The Effectiveness of Contextual-based InstructionalMaterials of Elements of Group 15 For Inorganic Chemistry - Agtri Wulandari; I Wayan Dasna; Surjani Wonorahardjo (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2019)
The purpose of research is determine the effectiveness of teaching materials based contextual elements of group 15 for the course of inorganic chemistry. The research design is one group pretest-posttet only. Subjects were students of Chemistry Education University of Palangka Raya as many as 47 people. Based on the research results, is obtained percentage of graduated postes amounted to 93.6%, mean of n-gain score is 0,54 (moderate), and the probability value (p) is 0,000, showed no significant difference between the pretest and posttest. Therefore, teaching materials element of group 15 based on contextual for inorganic chemistry course effective to improve student’s learning result.